The Impact of Using a Customized-Mobile Application on the Achievement of the University of Jordan English Students on English Syntax and their Attitudes towards the Application - Sadia Salem; Nayel Al-Shra'ah (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The present study aims at investigating the impact of using a customized-mobile application on the achievement of the University of Jordan English students on English Syntax and exploring their attitudes towards the application. Participants of the study were (74) UJ English students, who were distributed in two sections: a control group (37 students) and an experimental group (37 students). Two research instruments were used to collect data: an achievement test and an attitude questionnaire. Research findings revealed that the experimental group, who used the customized mobile application (Syntatopia app), showed significantly higher gains in their mean scores on the Syntax achievement test compared to those of the control group. Results also revealed that there were positive attitudes in all the questionnaire domains among the experimental group. Based on the findings, the researcher recommends that educators, curricula planners and application designers should  develop more course-based mobile applications for teaching and learning English syntax courses.